Perbedaan Informasi Anatomi Sekuen T1WI FSE dengan Fat Saturasi dan Tanpa Fat Saturasi pada Pemeriksaan MRI Kepala Irisan Axial Post Media Kontras - Dwi Kristiyanto; Mohamad Irwan Katili; Emi Murniati (Poltekkes Kemenkes Semarang, 2017)
Background: MRI of head post contrast media T1WI with Fat saturation the lesions appear bright whereas the organs around the fat looks darker. The purpose of this study was determine the difference in anatomical information of MRI Head FSE sequences T1 weighted axial slice using fat saturation and without fat saturation.Methods: This research is a quantitative research to determine differences in anatomical MRI information head with FSE sequences T1 weighted axial slice using Fat Fat Saturation Saturation and without air MRI on 1.5 T. The results are summarized and described to determine the value of anatomic information. Then proceed with the Wilcoxon test to see differences in anatomical information on T1 weighted MRI with Chief FSE And without Fat Fat Saturation Saturation.Result : The results obtained results description clearer criteria on the use of Fat Saturation is a pathological lesions without Fat Saturation is the maxillary sinus, orbit, skull base, CSF, Sulcus gyrus, cutis and sub cutis. For the p value is 0.108 (p 0.05) there was no significant difference MRI anatomical information chief weighted FSE T1 sequence axial pieces with Fat Saturation and without Fat SaturationConclusion : : From the analysis of quantitative seen that there are no differences in the anatomy of the head of information at the head MRI examination (p 0.05) between Fat saturation and Non Fat Saturation.